On T-Spline Classification (Journal of Computational Mathematics, 2022)
The present paper conjectures a topological condition which classifies a T-spline into standard, semi-standard and non-standard. We also provide the basic framework to prove the conjecture on the classification of semi-standard T-splines and give the proof for the semi-standard of bi-degree (1, $d$) and ($d$, 1) T-splines.